Harold : the Last of the Saxon Kings $1 (BVolume 05s - Lytton, Edward Bulwer Lytton, Baron, 1803-1873 (Salt Lake City, UT : Project Gutenberg, 2005)
"Harold: the Last of the Saxon Kings $1 (BVolume 05" by Lytton is a historical novel written during the Victorian era, a period noted for its rich literary output. This volume explores themes of love, ambition, and the turbulence of political power during the reign of King Edward the Confessor. The narrative delves into the life of Harold Godwinson, the last Anglo-Saxon king of England, as it captures the monumental conflict of a kingdom on the brink of change, fraught with both personal and political challenges. The story follows Harold as he navigates his responsibilities as a nobleman, the pressures of familial loyalty, and his deep love for Edith, a woman torn between her affections and religious obligations. As Harold faces the looming threat from foreign powers and the divisions within his own family, tensions rise with his brother Tostig and the challenges posed by rival claimants to the throne. The book weaves together Harold's aspirations for unity and strength in England, his struggles with fate as foretold by the enigmatic figure Hilda, and his passionate connection with Edith, ultimately setting the stage for high-stakes confrontations in a kingdom poised for destiny. As events unfold, the narrative highlights the interplay of fate, personal sacrifice, and the hoped-for revival of Saxon legacy amidst a shifting landscape. (This is an automatically generated summary.)s
Release date is 2005-03-01
This eBook was produced by Tapio Riikonen and David Widger
Keywords: Biographical fiction; Harold, King of England, 1022?-1066 -- Fiction; William I, King of England, 1027 or 8-1087 -- Fiction; Anglo-Saxons -- Kings and rulers -- Fiction; Great Britain -- History -- Edward, the Confessor, 1042-1066 -- Fiction; Great Britain -- Kings and rulers -- Fiction